Blood Pressure Trajectory Groups and Outcome After Endovascular Thrombectomy: A Multicenter Study. Issue 4 (16th November 2021) - Petersen, Nils H.; Kodali, Sreeja; Meng, Can; Li, Fangyong; Nguyen, Cindy Khanh; Peshwe, Krithika U.; Strander, Sumita; Silverman, Andrew; Kimmel, Alexandra; Wang, Anson; Anadani, Mohammad; Almallouhi, Eyad; et al.
Abstract : Background: Elevated blood pressure after endovascular thrombectomy (EVT) has been associated with an increased risk of hemorrhagic transformation and poor functional outcomes. However, the optimal hemodynamic management after EVT remains unknown, and the blood pressure course in the acute phase of ischemic stroke has not been well characterized. This study aimed to identify patient subgroups with distinct blood pressure trajectories after EVT and study their association with radiographic and functional outcomes. Methods: This multicenter retrospective cohort study included consecutive patients with anterior circulation large-vessel occlusion ischemic stroke who underwent EVT. Repeated time-stamped blood pressure data were recorded for the first 72 hours after thrombectomy. Latent variable mixture modeling was used to separate subjects into five groups with distinct postprocedural systolic blood pressure (SBP) trajectories. The primary outcome was functional status, measured on the modified Rankin Scale 90 days after stroke. Secondary outcomes included hemorrhagic transformation, symptomatic intracranial hemorrhage, and death. Results: Two thousand two hundred sixty-eight patients (mean age [±SD] 69±15, mean National Institutes of Health Stroke Scale 15±7) were included in the analysis. Five distinct SBP trajectories were observed: low (18%), moderate (37%), moderate-to-high (20%), high-to-moderate (18%), and high (6%). SBP trajectory group was independently associated with functional outcome at 90 days ( P <0.0001) after adjusting for potential confounders. Patients with high and high-to-moderate SBP trajectories had significantly greater odds of an unfavorable outcome (adjusted odds ratio, 3.5 [95% CI, 1.8–6.7], P =0.0003 and adjusted odds ratio, 2.2 [95% CI, 1.5–3.2], P <0.0001, respectively). Subjects in the high-to-moderate group had an increased risk of symptomatic intracranial hemorrhage (adjusted odds ratio, 1.82 [95% CI, 1–3.2]; P =0.04). No significant association was found between trajectory group and hemorrhagic transformation. Conclusions: Patients with acute ischemic stroke demonstrate distinct SBP trajectories during the first 72 hours after EVT that have differing associations with functional outcome. These findings may help identify potential candidates for future blood pressure modulation trials.